2018
DOI: 10.1080/00207543.2018.1484574
|View full text |Cite
|
Sign up to set email alerts
|

The role of modularity in the supply chain context: current trends and future research directions

Abstract: The aim of this editorial is to introduce the scope of the call for papers for the special issue. The submission statistics are then provided. A brief summary of the accepted papers is synthesised. The editorial ends with calls for future research in the areas of modularity and supply chain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The concept of modularity can also be applied to SCD (Pashaei and Olhager 2015). SCD modularity is also considered one of the most important strategic design attributes (Duclos, Vokurka, and Lummus 2003;Zhang, Huang, and Rungtusanatham 2008;Khan and Creazza 2009;Simchi-Levi 2013;Jayaram and Vickery 2018). It is important for lowering transaction costs by simplifying SC structures and reducing associated complexity.…”
Section: Product and Supply Chain Modularitymentioning
confidence: 99%
“…The concept of modularity can also be applied to SCD (Pashaei and Olhager 2015). SCD modularity is also considered one of the most important strategic design attributes (Duclos, Vokurka, and Lummus 2003;Zhang, Huang, and Rungtusanatham 2008;Khan and Creazza 2009;Simchi-Levi 2013;Jayaram and Vickery 2018). It is important for lowering transaction costs by simplifying SC structures and reducing associated complexity.…”
Section: Product and Supply Chain Modularitymentioning
confidence: 99%
“…Pine (1993) proposes that modularity is a product design architecture that meets customers’ specific demands and maintains low cost, meaning that it is a product design method that specifically focuses on addressing customers’ specific demands while managing cost constraints. Jayaram and Vickery’s (2018) recent summary on supply chain modularity states that modularity may increase product variety while decreasing product complexity. They also state that modularity enables many strategic programs within a supply chain, such as platform-based product development, agility, risk mitigation and sustainability.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Zhong et al [36] indicated that medical insurance goals should be positioned to common disease and frequently-occurring disease, so as to improve the basic rural medical and healthcare system accessibility and availability, especially to reduce the cost of treatment. Jayaram et al [37] found that when the marginal cost of medical services is high, the existence of medical insurance can increase the utility of patients.…”
Section: Literature Reviewmentioning
confidence: 99%